Variability of energy cost in breaststroke technique: a systematic review - Alves, M.; Barbosa, T. M.; Vilas-Boas, J. P. (Sports Biomechanics, 2025)
This study aimed to synthesise the body of knowledge on kinematics, active drag and energetics determinants of energy cost variability in the breaststroke technique. Methodological procedures considering the standards for systematic reviews according to the `"Preferred Reporting Items for Systematic Reviews and Meta-Analyses"` were employed. Searches were conducted in four prominent databases. A total of 1,464 articles were identified, of which 201 met the eligibility criteria. After evaluation, 73 articles were included for synthesis in this review. The included studies had a mean score (± SD) of 9.14 ± 1.76 points regarding the quality assessment. The present review identified three distinct domains of variables: kinematics (including stroke kinematics and coordination parameters), active drag, and energetics. The findings underscored the pivotal role of stroke kinematics, including stroke rate, stroke length, stroke index, and intra-cyclic variations of velocity, in influencing energy cost during breaststroke swimming. Additionally, the analysis highlighted the significance of propulsive and non-propulsive phases, arm-to-leg timing, and buoyancy in breaststroke technique. Notably, breaststroke exhibited higher values of active drag, frontal area, and energy cost, while maintaining lower velocity compared to other swimming techniques. Overall, this synthesis of literature highlights the holistic nature of energy cost in breaststroke swimming.